Robot-assisted endoscope guidance versus manual endoscope guidance in functional endonasal sinus surgery (FESS). (3rd October 2017) - Eichhorn, Klaus Wolfgang; Westphal, Ralf; Rilk, Markus; Last, Carsten; Bootz, Friedrich; Wahl, Friedrich; Jakob, Mark; Send, Thorsten
Abstract: Background: Having one hand occupied with the endoscope is the major disadvantage for the surgeon when it comes to functional endoscopic sinus surgery (FESS). Only the other hand is free to use the surgical instruments. Tiredness or frequent instrument changes can thus lead to shaky endoscopic images. Methods: We collected the pose data (position and orientation) of the rigid 0° endoscope and all the instruments used in 16 FESS procedures with manual endoscope guidance as well as robot-assisted endoscope guidance. In combination with the DICOM CT data, we tracked the endoscope poses and workspaces using self-developed tracking markers. Results: All surgeries were performed once with the robot and once with the surgeon holding the endoscope. Looking at the durations required, we observed a decrease in the operating time because one surgeon doing all the procedures and so a learning curve occurred what we expected. The visual inspection of the specimens showed no damages to any of the structures outside the paranasal sinuses. Conclusion: Robot-assisted endoscope guidance in sinus surgery is possible. Further CT data, however, are desirable for the surgical analysis of a tracker-based navigation within the anatomic borders. Our marker-based tracking of the endoscope as well as the instruments makes an automated endoscope guidance feasible. On the subjective side, we see that RASS brings a relief for the surgeon.